2007
DOI: 10.1243/09544054jem813sc
|View full text |Cite
|
Sign up to set email alerts
|

An optimal design approach for a cellular manufacturing system

Abstract: The current paper proposes an optimum clustering approach for automatic generation of machine cells and part families. The design of a cellular manufacturing system begins with a specified ‘part-machine incidence’ matrix, showing the machine sequence and volume of production. The arrangement of machines in the cells is addressed in the present paper by finding an optimal machine sequence, which maximizes the overall flow of components between the machines. An optimal number of cells is arrived heuristically by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…An optimal machine sequence, maximizing the overall flow of elements between the machines, is found out. 12 A Pareto-optimality-based multi-objective Tabu search (MOTS) algorithm is offered for the problem of machine-part grouping to incorporate objectives such as minimization of total cost, which consists of intracellular and intercellular transportation cost and machine investment cost, minimization of intracell loading unbalance and minimization of the intercell loading unbalance. 13 A new methodology for CF consuming a syntactic recognition approach is proposed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An optimal machine sequence, maximizing the overall flow of elements between the machines, is found out. 12 A Pareto-optimality-based multi-objective Tabu search (MOTS) algorithm is offered for the problem of machine-part grouping to incorporate objectives such as minimization of total cost, which consists of intracellular and intercellular transportation cost and machine investment cost, minimization of intracell loading unbalance and minimization of the intercell loading unbalance. 13 A new methodology for CF consuming a syntactic recognition approach is proposed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The result shown ACS outperformed existing GA method in several cases. Giri et al (2007) reported a TSP based heuristic embedded with ACO to form optimal part/machine clusters based on the overall machine sequence which leads to configurations with a minimum number of movements among the cells. The ACO is used here to obtain optimum machine sequence for maximum part volume flow.…”
Section: Aco In Cell Formationmentioning
confidence: 99%
“…Giri et al (2007) introduced the machine sequence assumption to the CFP, then developed a heuristic algorithm which finds, at first step, an optimal machine sequence maximizing the overall flow of parts between the machines, secondly, an optimal number of cells by regarding the total inter-cell movements using the obtained machine sequence. They showed that the grouping of parts and machines based on the overall machine sequence leads to assignments with a minimum number of movements between the cells.…”
Section: Introductionmentioning
confidence: 99%